INTEGRATING THE ARTS INTO SCIENCE TEACHING AND LEARNING - Kathy Cabe Trundle; Kathryn Green; Maria Shaheen (Sriwijaya University Learning and Education International Conference, 2016)
One way to enhance learners’ natural propensity for wonder andinterest in science is to integrate arts into science learning.Combining arts with science builds on students’ interests in naturewhile allowing them the joy and pleasure of artistic expression.Although educators often discuss integrating the arts into sciencelearning, empirical support is relatively recent (Gullatt, 2008).This study synthesizes previous empirical studies and theoreticalliterature published on arts integration, how the arts are integratedinto science teaching, and the efficacy of arts integration forscience learning.